Low cycle fatigue life prediction in shot‐peened components of different geometries—part I: residual stress relaxation. Issue 5 (13th October 2016) - You, C.; Achintha, M.; Soady, K. A.; Smyth, N.; Fitzpatrick, M. E.; Reed, P. A. S.
Abstract: In this study, the residual stress relaxation behaviour occurring during low‐cycle fatigue in shot‐peened specimens with either a flat or a notched geometry has been studied. A representative low‐pressure steam turbine material, FV448, was used. The residual stress and strain hardening profiles caused by shot peening were measured experimentally and were then incorporated into a finite element model. By allowing for both effects of shot peening, the residual stress relaxation behaviour was successfully simulated using this model and correlated well with the experimental data. Although more modelling work may be required to simulate the interaction between shot peening effects and external loads in a range of notched geometries, the model predictions are consistent with the specimens tested in the current study. The novelty of this study lies in the development of such a modelling approach which can be used to effectively simulate the complex interaction between shot peening effects and external loads in notched regions. Compared with the un‐notched geometry, the notched geometry was found to be more effective in retaining the improvement in fatigue life resulting from shot peening, by restricting the compressive residual stress relaxation during fatigue loading.